Enteroparasitoses in bovine herds from three rural properties in the metropolitan region of Vale do Paraíba - SP (Research, Society and Development, 2023)
The diagnosis of Cryptosporidium and other endoparasites is extremely important in cattle herds, as these diseases cause significant economic losses. In addition, they can cause serious impacts on the health and well-being of animals and humans, considering that the animal is a means of disseminating Cryptosporidium oocysts and other parasites. Tracking and early identification allows the implementation of appropriate control and treatment measures, preventing dissemination and ensuring production quality. In the present study, the occurrence of Cryptosporidium and other endoparasitosis in calves in three rural properties located in different municipalities in the Vale do Paraíba region was determined. For this purpose, fecal samples were processed using the Ritchie technique and subsequently stained using the modified Kynioum method. It was verified the positivity of 61.5% of parasites of the order Strongylidae and in relation to Cryptosporidium oocytes were not identified in the evaluated samples. It concludes a high number of infected calves and because they are eaily transmitted, it reinforces the importance of cleaning the environment and being careful with the health of the animals.